Foreign Debt and Literary Credit: Pablo Neruda and Walt Whitman. - AUSTIN, KELLY (Bulletin of Latin American Research, 2010)
The article draws in relief how translators carry with them cultural and ideological horizons that necessarily imbue their literary production with distinctly situated historical, political, and personal dimensions. It does so first by examining how The New York Times's translation of Pablo Neruda's 1972 address to the PEN Club reframes (or distorts) his views on political and literary issues ranging from the negotiation of the Chilean national debt to his literary indebtedness to Walt Whitman, and then by examining how Neruda's 1955 translation of Whitman's ‘Salut Au Monde!’, refashions and relocates Whitman's work, imbuing it with a communist ethos consistent with Neruda's own.